Deviation in the recovery of the lower limb and respiratory muscles of patients with polymyositis: a preliminary clinical study - Nishikawa, Yuichi (J Phys Ther Sci, 2016)
[Purpose] The purposes of this study were to quantify the serial changes in lower limb and respiratory muscle strengths and to evaluate the acute effects of physiotherapy in polymyositis patients. [Subjects and Methods] Five patients (57.6 ± 9.0 years, 50 to 72; four females) received physiotherapy five days a week for four weeks. The lower limb and respiratory muscle strength, the % vital capacity, and the Barthel index were evaluated at baseline and after the intervention. [Results] The patient’s symptoms and creatine kinase values did not change, and after four weeks, all of the patients exhibited significantly increased outcomes compared with the baseline. However, the inspiratory muscle strength of the patients presented smaller improvements than the expiratory muscle strength. [Conclusion] Differential changes in inspiratory and expiratory muscle strength were observed following physiotherapy, and an unbalanced muscle distribution may explain the pathological and therapeutic effects.